Submarine exposure guideline recommendations for carbon dioxide based on the prenatal developmental effects of exposure in rats. Issue 1 (3rd December 2018) - Howard, William R.; Wong, Brian; Yeager, Kimberly S. B.; Stump, Donald G.; Edwards, Tammye; Arden James, Richard; Goodwin, Michelle R.; Gargas, Michael L.
Abstract : Background: To protect crewmember health, the U.S. Navy sets exposure limits for more than 200 components of submarine atmospheres. The addition of females to nuclear submarines required a reevaluation of these exposure limits, originally established for all‐male crews. In the case of carbon dioxide (CO2 ), the only available data suitable for deriving an exposure limit were from a 2010 study sponsored by the British Royal Navy that reported a debatable interpretation casting doubt on whether current U.S. Navy exposure limits served to protect fetal developmental health. Methods: About 120 time‐mated female Sprague–Dawley rats (Crl: CD[SD]) were exposed to CO2 at levels of 1.5%, 2.0%, 2.5%, and 3.0% from gestation days 6 to 20. Dams were euthanized and fetuses were examined. Results: Findings with implications for exposure limits for CO2 during pregnancy were an increased mean litter proportion of early resorptions and a lower mean litter proportion of viable fetuses in the 3.0% CO2 group. Conclusion: The results yield a No Observed Adverse Effect Level (NOAEL) of 2.5% and a Lowest Observed Adverse Effect Level (LOAEL) of 3.0%. The results reasonably allow a point of departure of 2.5% CO2 for deriving an exposure recommendation. An interspecies uncertainty factor was applied to derive a recommended 90‐day continuous exposure limit (CEL) of 0.8% for CO2 . As reproductive endpoints that are developmental in nature must be assumed to result from a single exposure at a critical point during gestation, it is further recommended that the 24‐hr emergency exposure limit (EEL) also be 0.8%.